Comparing Digital and Non-Digital Gamification in Cooperative Learning: Effects of TGT with Wordwall and Question Cards on Students’ Mathematical Problem-Solving Ability - Astuti Astuti; Della Salvina (AL-ISHLAH: Jurnal Pendidikan, 2026)
Students’ mathematical problem-solving ability in Indonesia remains relatively low, partly due to the limited use of interactive and cooperative learning strategies in classrooms. The Teams Games Tournament (TGT) model, combined with instructional media, offers potential to enhance student engagement and problem-solving skills. This study aims to compare the effectiveness of TGT assisted by Wordwall, TGT assisted by question cards, and conventional learning in improving students’ mathematical problem-solving ability. This study employed a quasi-experimental design with a posttest-only control group. The sample consisted of three seventh-grade classes selected through purposive sampling, each comprising 20 students. The first experimental group was taught using TGT assisted by Wordwall, the second experimental group used TGT assisted by question cards, and the control group received conventional instruction. Data were collected using a validated and reliable essay test and analyzed through descriptive statistics, normality and homogeneity tests, followed by Welch ANOVA and Games–Howell post hoc analysis. The results revealed significant differences among the three groups (p 0.05). The highest mean score was achieved by the TGT with question cards group (M = 89.60), followed by TGT with Wordwall (M = 77.00), while the control group obtained the lowest mean score (M = 54.70). These findings indicate that both TGT-based approaches are more effective than conventional learning, with question card assistance producing the most substantial improvement. In conclusion, while digital media such as Wordwall can enhance learning, non-digital approaches that promote deeper cognitive engagement may yield better outcomes in developing mathematical problem-solving skills.